Efek Pemberian Formulasi Pupuk Semi Organik dan Populasi Bayam Merah (Amaranthus spp. L) terhadap Hasil Bayam Merah dan Perubahan Sifat KimiaTanah Inceptisol - GDE CAKRA WAHYU P; A.A. NYOMAN SUPADMA; I DEWA MADE ARTHAGAMA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
The Effect of Semi-Organic Fertilizer Formulation on Red Spinach Populations (Amaranthus spp.L) on Yield and Changes in Inceptisol Soil Chemical Properties This study aims to determine the proper formulation of organic, inorganic and biological fertilizers and the best population to increase the production of spinach on Inceptisol soil, as well as changes in soil chemical properties after harvest. This research was conducted from December 2019 to March 2020 in Samplangan Village, Gianyar Regency, using a pot experiment. The second stage is analysis the chemical properties of soil which is carried out at the Laboratory of Soil and Environmental Sciences, Faculty of Agriculture, Udayana University. The design used was a randomized block design (RBD) with nested patterns with 5 formulations and 2 different populations with 3 replications. F0 = without fertilizer (control), F1 = (3 tons of compost + 350 kg of urea + 5 cc of biofertilizer. 1 l-1 water) hectare-1, F2 = (6 tons of compost + 300 kg of urea + 10 cc of biofertilizer. 1 1-1 water) hectare-1, F3 = (9 tons of compost + 250 kg urea + 15 cc of biofertilizer. 1 l-1 water) hectare-1, F4 = (12 tons of compost + 200 kg of urea + 20 cc of biofertilizer. 1 l-1 water) hectare-1, P1 5 plants and P2 10 plants. Treatment F2 and F3 produced the highest fresh weight compared to control in population P1, while in population P2 treatment F3 produced the highest fresh weight. Provision of semi-organic fertilizer formulations can increase the content of nutrient elements contained in the soil after harvest.